2021
DOI: 10.1109/mitp.2020.3016488
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Pronged View on Organizational Agility

Abstract: The ability of organizations to sense and respond to changes-defined as organizational agilityis considered by senior executives among their top information technology (IT) concerns as an important ability for organizations on their quest toward sustained competitive advantage.However, every transformation toward agility also comes at a cost, requiring resource commitment and IT landscape changes. We present examples of successful and unsuccessful attempts at achieving agility while leveraging IT. Our presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For practitioners, IT-enabled organizational agility now represents a top concern (Werder et al, 2021). Meanwhile, researchers as well as some experts close to SMEs are increasingly inclined to question whether all SMEs' IT projects are true digital transformation projects.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For practitioners, IT-enabled organizational agility now represents a top concern (Werder et al, 2021). Meanwhile, researchers as well as some experts close to SMEs are increasingly inclined to question whether all SMEs' IT projects are true digital transformation projects.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…In the same line of thought, there are also gaps concerning why, when and how IT capabilities become 'dynamic' (or not) (Li & Chan, 2019), and under what specific conditions they manifest themselves (Ozanne et al, 2022). This is why ITenabled organizational agility now represents a top concern for all the actors involved in such a context (Werder et al, 2021), and constitutes a core mechanism for strategic renewal (Warner & Wäger, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Karimi and Walter (2021) found that EA directly influences the development of digital platform capacities for the business model and product innovation. The findings of Werder et al (2021) show that EA may greatly enhance process and product performance. The results of Hosseini, Alizadeh, and Abedi (2019) revealed that EA was positively and significantly linked with human resources management.…”
Section: Entrepreneurial Agility (Ea) and Organizational Performance ...mentioning
confidence: 96%
“…Managers who play the role of entrepreneurs must find digital tools and procedures that improve distance communication and innovation. Werder et al [43] stress the importance of adaptability to the changing environment, especially in times of a pandemic, making strategic choices for telework vital. As disturbances can arise due to communication gaps, the role of a disturbance handler necessitates swift virtual conflict resolution.…”
Section: Leaders and Teleworkmentioning
confidence: 99%